Electrothermal Analysis of a MetalMUMPs Device for Acetone Detection - Ahmed, A.Y. (Institute of Electrical and Electronics Engineers Inc., 2019)
Acetone is used extensively in workplaces, and hence detection of acetone leak is important to avoid its health and safety risks. Acetone concentration (>176 parts per million (ppm)) acetone in air is also toxic and can cause damage to human vital organs. The most common used sensors for acetone vapor are based on metal oxide semiconductor sensors, which have issues of sensitivity and working at higher temperatures. Microelectromechanical systems (MEMS) based sensors are a good alternative for acetone sensing due to small size, high sensitivity and working at low temperatures. The main objective of this paper is to report electrothermal analysis of MEMS based MetalMUMPs device that have been fabricated and utilized for acetone vapor sensing. The device is actuated by electrothermal technique through embedding a meander type microheater. The microheater made of polysilicon of a length, width and thickness of 4877\ \boldsymbolμ\mathbfm,\ 5 \boldsymbolμ \mathbfm and 0.7\ \boldsymbolμ \mathbfm, respectively. The device was actuated using voltage in the range of 0.71 - 3.54 V and the resulted current was found to be in the range of 33 -162\ \boldsymbolμ \mathbfA. Due to this small current, the dissipation power was found to be very low in the range of 23- 583\ \boldsymbolμ \mathbfW. This yields to such small temperature changes in the range of 0.12 - 2.88 Â°K, which was found to be enough to actuate the device and give the output signal change due to acetone vapor concentration change. The time constant for the microheater temperature rise or fall was found to be 1.44 ms. CoventorWare simulation software 2008 was used to design and simulate the electrothermal physics of the device, and the simulation results were compared with the modeling results where the results were found to be in a good agreement within 0.34 - 1.9 . Â© 2019 IEEE.